Perbedaan Karakteristik Makiyah dan Madaniah dalam Perspektif Komunikasi antarbudaya - Ulya Hilalatul Hasbi; Swandi Yusuf; Muhammad Sa'i; Muhammad Habiburrahman (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
This research examines the role of intercultural communication in understanding the context of Qur'anic revelation in the Makkah and Madinah periods. The aim is to analyze the differences in the characteristics of Makiyah and Madaniah verses and the influence of the socio-cultural context on communication patterns and the delivery of revelation. This research uses a literature study research design with a qualitative approach. The research data is in the form of secondary data obtained through data collection techniques using documentation studies from various sources such as tafsir books, Qur'anic literature, and intercultural communication theories. Data analysis was conducted using content analysis and hermeneutic interpretation techniques. The results showed that communication in the Makkah period used a strong and brief language style according to the context of Arab society, while the Medina period was more detailed and explicit. Differences in the socio-cultural context influenced communication strategies, where Makkah focused on strengthening the faith, while Medina on the formation of social systems. Communication channels evolved from oral dominance in Makkah to a combination of oral and written in Medina. This research proves that intercultural communication theory can be used as an analytical framework to understand the dynamics of Qur'anic revelation. This understanding is important for developing contemporary da'wah methods that are adaptive to cultural diversity.